The language-in-education politics in Nigeria. Issue 5 (2nd September 2016) - Igboanusi, Herbert; Peter, Lothar
Abstract : Against the backdrop of the rejection of mother tongue-based bilingual education in Southern Nigeria and in Northern linguistic minority areas, this study investigates the micropolitics of language education by interrogating everyday language practices of education stakeholders which are at variance with language-in-education policy. It relied on a wide range of data collected through carefully documented observations of classrooms and school community language practices, semi-structured interviews with publishing managers, informal interviews with teachers as well as a questionnaire survey (covering a comprehensive cross-section of stakeholders across the country). Findings suggest that only a uniformly implemented education policy in all schools across the country can restore the use of Nigeria's indigenous languages as media of instruction in primary schools. The study recommends a combination of advocacy and research findings to get the policy-makers and education stakeholders to accept first language-based (or L1 based) educational reform.